ANALISIS TEORI PENETRASI SOSIAL DALAM APLIKASI DATING (STUDI PADA APLIKASI TINDER) - Aldin, Fadli fajar; Yusuf, Dzulfahira; Azzahra, Amalia; Syarifudin, Ali; Syafitri, Wiena (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Developing technology provides changes in all aspects of human life, including interacting and communicating between individuals. Technological developments cannot be separated from the internet, it is a necessity that is often used by humans today, the internet makes it easy for humans to interact and communicate without the limits of space and time. The internet is also very easy to access by anyone, anytime and anywhere. Now, every human can interact and communicate through computers and telephones which are connected to the internet. It is not surprising that many people establish interpersonal relationships through computers and telephones without meeting face to face. Technological developments can be accessed through the internet, which are capable of creating applications such as online dating or datting apps with the aim of facilitating interaction and communication in finding someone to talk to or establishing a more intimate relationship. In online dating applications, several stages are found, where individuals have the eager to convey self-information to other individuals. This study aims to determine the existence of social penetration theory on interaction and communication in online dating apps. This research found a process or stage that exist in online dating applications when interacting and communicating between individuals happened. This research uses a qualitative approach with a method through literature study by searching books, journals and scientific articles that can be obtained from electronic media such as internet, Google Scholar, Google Books